23. SOME FACTORS RELATED TO THE RISK OF FALLING OF PATIENTS RECEIVING INPATIENT TREATMENT AT THANH NHAN HOSPITAL NEUROLOGY DEPARTMENT (Vietnam Journal of Community Medicine, 2024)
Objective: Analyze a number of factors related to the risk of falls of inpatients in the Department of Neurology, Thanh Nhan Hospital in 2024.Subjects and methods of the study: Cross-sectional description of over 150 patients treated inpatient of Neurology Department at Thanh Nhan Hospital with a set of questions to interview patients to assess the risk of falling on the Johns Hopkins (JHRAT) scale.Results: The percentage of patients with a score of < 14 points (low risk of falling) accounted for 58.7%; patients with a score of ≥ 14 points (high risk of falling) accounted for 41.3% and this rate was higher in patients with BMI ≥ 18.5 kg/m2 compared to BMI < 18.5 kg/ m2 (45.2% compared to 20.8%) , patients with different occupations compared to retirement patients (52.5% compared to 33.7%), patients with neuropathy compared to no disease (54.8% compared to 36.1%).Conclusion: The high risk of falling of the study subjects accounted for 41.3% and this rate was higher in patients with BMI ≥ 18.5 kg/m2, patients of working age, patients with neurological diseases.
Keywords: risk of falls; neurology; related factors